2018
DOI: 10.1021/acs.est.8b00512
|View full text |Cite|
|
Sign up to set email alerts
|

Organohalogens Naturally Biosynthesized in Marine Environments and Produced as Disinfection Byproducts Alter Sarco/Endoplasmic Reticulum Ca2+ Dynamics

Abstract: Contemporary sources of organohalogens produced as disinfection byproducts (DBPs) are receiving considerable attention as emerging pollutants because of their abundance, persistence, and potential to structurally mimic natural organohalogens produced by bacteria that serve signaling or toxicological functions in marine environments. Here, we tested 34 organohalogens from anthropogenic and marine sources to identify compounds active toward ryanodine receptor (RyR1), known toxicological targets of non-dioxinlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 77 publications
1
29
0
Order By: Relevance
“…TBP has been implicated as an inducer of coral metamorphosis by testing the effect of fractionated and purified TBP on coral larvae (Tebben et al ., 2011, 2015; Sneed et al ., 2014). To determine whether larvae of Hydractinia respond to purified TBP in a similar manner, we investigated whether synthesized, exogenously added TBP (Zheng et al ., 2018) at similar concentrations to those tested for corals (Sneed et al ., 2014; Tebben et al ., 2015) stimulates Hydractinia metamorphosis. The development of Hydractinia larvae after exposure to TBP or bacteria was quantified after 72 h and scored positively for metamorphosis if they developed stolons and tentacles (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…TBP has been implicated as an inducer of coral metamorphosis by testing the effect of fractionated and purified TBP on coral larvae (Tebben et al ., 2011, 2015; Sneed et al ., 2014). To determine whether larvae of Hydractinia respond to purified TBP in a similar manner, we investigated whether synthesized, exogenously added TBP (Zheng et al ., 2018) at similar concentrations to those tested for corals (Sneed et al ., 2014; Tebben et al ., 2015) stimulates Hydractinia metamorphosis. The development of Hydractinia larvae after exposure to TBP or bacteria was quantified after 72 h and scored positively for metamorphosis if they developed stolons and tentacles (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Studies of TBP exposure to phytoplankton reveals that TBP induces the release of intracellular calcium stores (Whalen et al ., 2018). TBP exposure to mammal microsomes triggers Ca 2+ efflux by activating the Ryanodine receptor, RyR1, and inhibiting microsomal sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase, SERCA1a (Zheng et al ., 2018). Calcium signalling and membrane potential depolarization have been linked to the induction of Hydroides metamorphosis (Carpizo‐Ituarte and Hadfield, 1998; Holm et al ., 1998; Chen et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…huxleyi genome has an inositol 1,4,5-triphosphate receptor (ITPR) containing a protein architecture characteristic of canonical metazoan members of this superfamily 47 . Moreover, a recent study found that halogenated pyrroles, including TBP of marine origin, were modulators of mammalian ryanodine receptors 48 . These authors also noted that the pyrrole moiety at 2-position on the diterpenoid ryanodine was essential for both high-affinity binding to RyR1 and conferring toxicity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…While PCBs are among the most extensively studied POP chemotype, other major POPs have been shown to have neuropathogenic potential, including organochlorine insecticides (e.g., DDT, cyclodienes, hexachlorocyclohexanes) and, more recently, polybrominated diphenyl ether flame retardants (PBDEs) and newly discovered organohalogens produced as disinfectant byproducts [96,146,223]. Figure 1 compares PCBs with chemotypes that have emerged more recently as POPs of human health concern because of their potential as neuromodulators and neurotoxicants.…”
Section: Introductionmentioning
confidence: 99%